Note—Managing Sickle Cell Anemia in Zaire - Lemaire, Jean (Management Science, 1979)
This paper analyzes the long term effects of various genetic policies that could be applied at a national level in Zaire to fight sickle cell anemia: the prohibition of marriages between individuals with the sickle cell trait, increased efficacy of the medical cure of sickle cell anemia, selective birth control, and eradication of malaria. We show that combined application of the last two policies would lead to progressive disappearance of the disease. The first two policies lead to disastrous effects in the long run, since the proportion of those who have the sickle cell trait would increase from the present 25%. Due to major differences between Zaire and the United States, the results differ markedly from those of Meredith (Meredith, J. 1977. Managing the incidence of sickle cell Anemia through genetic counseling. Management Sci. 23 1261–1272.) who presented the results of a similar study in the United States in a previous article in Management Science.